Endoskopsko paliativno zdravljenje raka danke: naše izkušnje z laserjem - Pernat Drobež, Cvetka (Zdravniški vestnik, 2006)
Background. The palliative treatment of patients suffering from an incurable cancer is a common problem. In cases of advanced rectal cancer the therapeutic aims are elimination or prevention of obstruction, bleeding and pain and improvement in quality of life. The aim of our study was to evaluate the role of laser in the endoscopic palliative treatment of rectal cancer. Patients and methods. 44 patients with inoperable rectal cancer were treated with laser from 1998 to 2005. The indication for treatment included stenosis, bleeding and/or pain. Results. Recanalisation and haemostasis were achieved in 37 patients (84 %). In 7 patients (16 %) we were unsuccessful. We observed 4 serious but nonfatal complications in form of rectal perforations with inflammation. None of them needed surgical attention. Conclusions. Endoscopic laser therapy is an effective and well tolerated method in palliation of rectal cancer with low risk of complications.
Keywords: danka; Endoscopy; Endoskopija; laser; Laserji; Lasers; paliativno zdravljenje; rak (medicina); Rectal Neoplasms; Rektalne novotvorbe; therapy; Zdravljenje